(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Obstructive sleep apnea (OSA) is a common sleeping disorder characterized by the temporal partial or complete obstruction of the upper airway during sleep. Simulating airflow and resulting deformation can help to understand the causes that lead to OSA and help to improve therapy options. In this work, the interaction between airflow and the surrounding soft tissue of an upper airway model including the nasal structures was examined with a fluid-structure interaction (FSI) simulation. The simulation was validated with experimental measurements. Therefore, an anthropomorphic 3D printed upper airway phantom of an obstructive sleep apnea patient was fabricated and used in deformation measurements to reproduce an inhalation process with a maximal flow rate of 15 l/min. The deformation was measured with a CT scanner and compared to the corresponding FSI simulation results. The comparison showed good agreement in the resulting deformation.